Mereproduksi Citra, Mencari Legitimasi: Analisis Peran Biro Humas dalam Dinamika Sosial-Politik Pemerintah Daerah - Hattu, Beatrix; Telussa, Sandra Ivonnie (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This study aims to analyze the strategic role of the Public Relations Bureau in reproducing public image and seeking political legitimacy for local government amidst dynamic socio-political change, focusing on the Provincial Government of Maluku. Employing a qualitative approach, the research was conducted in Ambon City through in-depth interviews, participatory observation, and document analysis within the Public Relations Bureau of the Maluku Governor's Office. The findings reveal that the Bureau has not effectively implemented public relations strategies to maintain and enhance the government’s image. Key obstacles include the inability to translate policies into public narratives, failure to adapt to evolving social dynamics, and weak two-way communication with stakeholders. Additionally, public relations personnel lack the analytical capacity to interpret socio-political trends or provide strategic recommendations to leadership. These shortcomings indicate that the Bureau’s role as a key actor in perception management and legitimacy-building remains suboptimal. The novelty of this study lies in its integrative approach, combining political communication theory and institutional dynamics at the local level, offering fresh insights into state-society relations through strategic communication. The study recommends strengthening institutional capacity and professionalizing public relations functions to meet the demands of contemporary political communication in local governance.